Targeting the mTOR pathway uncouples the efficacy and toxicity of PD-1 blockade in renal transplantation - Khashayar Esfahani (Nature Portfolio, 2019)
The use of immune checkpoint inhibitors (ICI) in cancer patients with solid organ allografts is hampered due to potential organ rejection. Here, the authors present a case report of a patient with kidney allograft and show that treatment with the mTOR inhibitor sirolimus preserves peripheral tolerance and anti-tumour efficacy of ICI therapy.